The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fpsyg.2022.998536
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and self-efficacy in Chinese international students’ L3 French learning with L2 English and L3 French

Abstract: The present study explored the relationship between international students’ Third Language Anxiety (TLA) and self-efficacy. The research data were collected through questionnaires involving 243 Chinese International students’ L3 French Learning with L2 English and L3 French at one university in the U.K. Three of them were interviewed about their experience of anxiety and self-efficacy. Major findings include four underlying factors correlated with TLA and two underlying factors correlated with self-efficacy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The four factors that emerged in this research carry little resemblance to the factors that have been proposed in studies by Arnaiz and Guillen (2012), Aslan and Thompson (2018), Bensalem and Thompson (2022), Cheng et al (1999), La darević (2021), Lin (2022), Liu and Yuan (2021), Mak (2011), Park (2014), Phongsa et al (2017), Thompson and Khawaja (2015), Lee (2013, 2014), Thompson and Sylvén (2015), and Tóth (2008). Among these 18 studies, the emergent factors comprised different items and were named differently from those in our study.…”
Section: Factor Analyses In This and Other Researchmentioning
confidence: 62%
See 1 more Smart Citation
“…The four factors that emerged in this research carry little resemblance to the factors that have been proposed in studies by Arnaiz and Guillen (2012), Aslan and Thompson (2018), Bensalem and Thompson (2022), Cheng et al (1999), La darević (2021), Lin (2022), Liu and Yuan (2021), Mak (2011), Park (2014), Phongsa et al (2017), Thompson and Khawaja (2015), Lee (2013, 2014), Thompson and Sylvén (2015), and Tóth (2008). Among these 18 studies, the emergent factors comprised different items and were named differently from those in our study.…”
Section: Factor Analyses In This and Other Researchmentioning
confidence: 62%
“…Although responses on the FLCAS are often added (after reverse coding the positively worded items) to form a single score that represents FLA as a global, homogeneous construct (see, e.g., Allen & Herron, 2003; Arnaiz & Guillén, 2012; Dewey et al., 2018; Lim & Low, 2017), a number of researchers have attempted to determine whether the scale comprises separate factors. Their studies have suggested that, within the FLCAS, there are two factors (Bensalem & Thompson, 2022; Cheng et al., 1999; Park, 2014); three factors (Arnaiz & Guillen, 2012); four factors (Aslan & Thompson, 2018; Lin, 2022; Thompson & Khawaja, 2016; Thompson & Lee, 2013, 2014); two, three, or four factors (Tóth, 2008); five factors (Lađarević, 2021; Mak, 2011); six factors (Phongsa et al., 2017; Thompson & Sylvén, 2015); and six or seven factors (Liu & Yuan, 2021). The factor composition of the FLCAS, therefore, appears to be highly inconsistent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Foreign language anxiety is a multifaceted phenomenon encompassing different dimensions such as fear of negative evaluation, communicative apprehension, and test anxiety [5][6][7][8].…”
Section: The Overview Of Anxietymentioning
confidence: 99%
“…This study will build on Bandura's theory of self-efficacy. Self-efficacy is defined as a belief that an individual has in his or her own ability to produce desired behaviors, and it can also be understood as the subjective judgment of whether people can successfully engage in a certain achievement behavior [9]. This study combines quantitative and qualitative research methods to explore the relationship between the usage of ChatGPT and the learning efficacy of Chinese college students.…”
Section: Introductionmentioning
confidence: 99%